2017
DOI: 10.1155/2017/4812637
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of Prognostic Factors in Multiple Myeloma

Abstract: Multiple myeloma (MM) is a heterogeneous hematologic malignancy involving the proliferation of plasma cells derived by different genetic events contributing to the development, progression, and prognosis of this disease. Despite improvement in treatment strategies of MM over the last decade, the disease remains incurable. All efforts are currently focused on understanding the prognostic markers of the disease hoping to incorporate the new therapeutic modalities to convert the disease into curable one. We prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
40
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(46 citation statements)
references
References 103 publications
1
40
0
1
Order By: Relevance
“…Nonazotemic dogs also had a longer survival compared with azotemic dogs, but this difference was not statistically significant . In contrast, studies of MM in humans have not consistently found hypercalcemia, osteolytic lesions, and Bence‐Jones proteinuria to be prognostic, and instead use risk stratification models that primarily rely on cytogenetics, gene expression profiling, the International Staging System, and serum lactate dehydrogenase activity as prognostic markers . Other studies have evaluated factors such as renal disease, neutrophil‐to‐lymphocyte ratio (NLR), platelet‐to‐lymphocyte ratio (PLR), and anemia, which have negatively affected outcome.…”
Section: Introductionmentioning
confidence: 99%
“…Nonazotemic dogs also had a longer survival compared with azotemic dogs, but this difference was not statistically significant . In contrast, studies of MM in humans have not consistently found hypercalcemia, osteolytic lesions, and Bence‐Jones proteinuria to be prognostic, and instead use risk stratification models that primarily rely on cytogenetics, gene expression profiling, the International Staging System, and serum lactate dehydrogenase activity as prognostic markers . Other studies have evaluated factors such as renal disease, neutrophil‐to‐lymphocyte ratio (NLR), platelet‐to‐lymphocyte ratio (PLR), and anemia, which have negatively affected outcome.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3]8] While Durie-Salmon staging includes the M-protein level in establishing tumor burden, [9] the ISS is based solely on the albumin and β2-microglobulin levels. [4] However, the association of the globulin level with treatment response and OS had not been previously investigated.…”
Section: Discussionmentioning
confidence: 99%
“…The prognostic indicators help to determine the rate of growth of the tumor, the extent of metastasis, the biologic make-up of the tumor, the response to therapy, and the overall survival rate of the patients. The prognosis of MM often depends on the stage of the disease, whether a certain immunoglobulin is present, the extent of involvement of the kidney, the response of the tumor to the initial treatment, the recurrence of the tumor, the age and general health of the patient [42]. Also, the prognosis is variable according to the type of treatment used.…”
Section: Prognosis Of MMmentioning
confidence: 99%